Nanostructured Metal Oxides and Sulfides for Lithium–Sulfur Batteries - Liu, Xue; Huang, Jia‐Qi; Zhang, Qiang; Mai, Liqiang (Advanced materials (Weinheim), 2017)
Lithium–sulfur (Li–S) batteries with high energy density and long cycle life are considered to be one of the most promising next‐generation energy‐storage systems beyond routine lithium‐ion batteries. Various approaches have been proposed to break down technical barriers in Li–S battery systems. The use of nanostructured metal oxides and sulfides for high sulfur utilization and long life span of Li–S batteries is reviewed here. The relationships between the intrinsic properties of metal oxide/sulfide hosts and electrochemical performances of Li–S batteries are discussed. Nanostructured metal oxides/sulfides hosts used in solid sulfur cathodes, separators/interlayers, lithium‐metal‐anode protection, and lithium polysulfides batteries are discussed respectively. Prospects for the future developments of Li–S batteries with nanostructured metal oxides/sulfides are also discussed. Nanostructured metal oxides and sulfides are considered as polysulfide anchoring sites in working Li–S batteries for the battery's high sulfur utilization and long life span. The relationships between the intrinsic properties of the metal oxide/sulfide hosts and the electrochemical performances of Li–S batteries are reviewed.